A fibrin based model for rheumatoid synovitis. Issue 12 (21st November 2003) - Sánchez-Pernaute, O; Largo, R; Calvo, E; Alvarez-Soria, M A; Egido, J; Herrero-Beaumont, G
Abstract : Intracavitary fibrin clots may initiate pannus formation and the immunopathology of RA. Two critical steps, probably host dependent, may determine the development of RA: an altered regulation of extravascular haemostasis or an aberrant reactivity of synovial fibroblasts to the adhered fibrin clots. Current treatments for RA target events downstream of fibrin deposition, perhaps agents acting at an earlier stage should be tried.